The effect of expiratory flow limitation on supine persistent hyperinflation in COPD: a prospective observational study - Meera Srinivasan; Hannah Pollard; David G. Chapman; Katrina Tonga; Kieran Patel; Kaj Blokland; David Touma; Cindy Thamrin; Troy Cross; Kim Prisk; Gregory G. King (ERJ Open Research)
Introduction COPD is characterised by airflow obstruction, expiratory airway collapse and closure causing expiratory flow limitation (EFL) and hyperinflation. Supine posture may worsen ventilatory function in COPD, which may cause hyperinflation to persist and contribute to symptoms of orthopnoea and sleep disturbance. Our aim was to determine the impact of supine posture on hyperinflation, dynamic elastance and EFL in COPD and healthy subjects. We hypothesised that changes in hyperinflation in supine posture are influenced by EFL and gas trapping in COPD. Methods Clinically stable COPD patients (compatible symptoms, smoking >10 pack-years, obstructed spirometry) and healthy controls underwent oscillometry in the seated and supine positions. Hyperinflation was measured by inspiratory capacity (IC) and the ratio of IC to total lung capacity (IC/TLC) while seated and supine EFL was measured as the difference in mean inspiratory and mean expiratory oscillatory reactance at 5 Hz (Xrs5). Relationships between IC, IC/TLC and Xrs5, were examined by Spearman correlation. Results 42 COPD patients demonstrated no change in IC/TLC from seated (0.31 L) to supine (0.32 L) position (p=0.079) compared to significant increases seen in 14 control subjects (0.37 L seated versus 0.44 L supine; p<0.001). In COPD, worse dynamic elastance (Xrs5 rs 0.499; p=0.001) and EFL (ΔXrs5 rs −0.413; p=0.007), along with increased age and lower body-mass-index were predictors of supine hyperinflation. Conclusion Supine persistent hyperinflation occurs in COPD and is associated with increased dynamic elastance and EFL, likely the result of increased airway closure due to gravitational redistribution of lung mass.